The Influence of the Gender Asterisk (“Gendersternchen”) on Comprehensibility and Interest - Friedrich, Marcus C. G.; Drößler, Veronika; Oberlehberg, Nicole; Heise, Elke (Frontiers in Psychology, 2021)
Recently, the gender asterisk (“Gendersternchen”) has become more widespread in grammatical gender languages in order to represent all genders. Such gender-fair language is intended to help better address women and other genders and make their interests and achievements more visible. Critics often argue this would make the language less comprehensible and less aesthetically appealing. Two experiments examined the effects of the gender asterisk on text comprehensibility, aesthetic perception and interest. N = 159 and N = 127 participants were randomly provided with a text in either masculine-only form or alternatively in gender-fair language with the gender asterisk. The results of the first experiment showed no impairment of comprehensibility and aesthetic evaluation of the texts by the gender asterisk and no effect on interest in the game, while the second experiment showed significant impairments of comprehensibility, aesthetic evaluation, and interest in the game by the gender asterisk. The proportion of singular forms is discussed as a possible explanation for the different results. Experiment 1 predominantly used plural forms like die Spieler*innen, ~“the fe*male players” and did not include forms such as der*die Spieler*in, “the*the ~fe*male player”), whereas Experiment 2 included many such more complex singular forms. We argue that this issue might be crucial, and that it deserves full attention in future studies.